Investigation of hippocampal substructures in focal temporal lobe epilepsy with and without hippocampal sclerosis at 7T. Issue 5 (26th August 2016) - Santyr, Brendan G.; Goubran, Maged; Lau, Jonathan C.; Kwan, Benjamin Y.M.; Salehi, Fateme; Lee, Donald H.; Mirsattari, Seyed M.; Burneo, Jorge G.; Steven, David A.; Parrent, Andrew G.; de Ribaupierre, Sandrine; Hammond, Robert R.; et al.
Abstract : Purpose: To provide a more detailed investigation of hippocampal subfields using 7T magnetic resonance imaging (MRI) for the identification of hippocampal sclerosis in temporal lobe epilepsy (TLE). Materials and Methods: Patients ( n  = 13) with drug‐resistant TLE previously identified by conventional imaging as having hippocampal sclerosis (HS) or not (nine without HS, four HS) and 20 age‐matched healthy controls were scanned and compared using a 7T MRI protocol. Using a manual segmentation scheme to delineate hippocampal subfields, subfield‐specific volume changes and apparent transverse relaxation rate ( R 2 * ) were studied between the two groups. In addition, qualitative assessment at 7T and clinical outcomes were correlated with measured subfield changes. Results: Volumetry of the hippocampus at 7T in HS patients revealed significant ipsilateral subfield atrophy in CA1 ( P  = 0.001) and CA4+DG ( P < 0.001). Volumetry also uncovered subfield atrophy in 33% of patients without HS, which had not been detected using conventional imaging. R 2 * was significantly lower in the CA4+DG subfields ( P  = 0.001) and the whole hippocampus ( P  = 0.029) of HS patients compared to controls but not significantly lower than the group without HS ( P  = 0.077, P  = 0.109). No correlation was found between quantitative volumetry and qualitative assessment as well as surgical outcomes (Sub, P  = 0.495, P  = 0.567, P  = 0.528; CA1, P  = 0.104 ± 0.171, P  = 0.273, P  = 0.554; CA2+CA3, P  = 0.517, P  = 0.952, P  = 0.130 ± 0.256; CA4+DG, P  = 0.052 ± 0.173, P  = 0.212, P  = 0.124 ± 0.204; WholeHipp, P  = 0.187, P  = 0.132 ± 0.197, P  = 0.628). Conclusion: These preliminary findings indicate that hippocampal subfield volumetry assessed at 7T is capable of identifying characteristic patterns of hippocampal atrophy in HS patients; however, difficulty remains in using imaging to identify hippocampal pathologies in cases without HS. Level of Evidence : 2 J. MAGN. RESON. IMAGING 2017;45:1359–1370